2018
DOI: 10.1159/000484988
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dental Caries and BMI in Children: A Systematic Review and Meta-Analysis

Abstract: Research on the association between dental caries and body mass index (BMI) in children has shown contradictory results; thus we aimed to examine the association between dental caries and the full range of BMI classes among children. We comprehensively searched PubMed, Embase, and the Cochrane Library for studies published prior to March 2017. Articles comparing dental caries among the full range of BMI classes for children below 18 years of both genders were included. Fourteen studies were eligible for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
116
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(132 citation statements)
references
References 31 publications
13
116
1
2
Order By: Relevance
“…A recent systematic literature review demonstrated a lack of significant differences in dental caries prevalence between abnormal‐ and normal‐weight children and adolescents, in both dentitions. The authors, however, suggest the importance of investigating the confounding factors associated between dental caries and body mass index (BMI) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic literature review demonstrated a lack of significant differences in dental caries prevalence between abnormal‐ and normal‐weight children and adolescents, in both dentitions. The authors, however, suggest the importance of investigating the confounding factors associated between dental caries and body mass index (BMI) …”
Section: Introductionmentioning
confidence: 99%
“…Up to date, most studies of the relationship between caries experience and overweight/obese children used the DMF index (decayed, missing, and filled), proposed by the World Health Organization (WHO) . This index, however, does not evaluate the level of severity of dental caries, thereby providing inaccurate results . Yet, the use of validated criteria seems to improve the accuracy of visual inspection .…”
Section: Introductionmentioning
confidence: 99%
“…Hooley et al concluded in their systematic review that both high and low BMI are associated with children's dental caries. Similarly, the association was also inconclusive in another systematic review, particularly concerning low‐ and middle‐income countries as well as primary and permanent dentitions . Both dental caries and obesity are multifactorial and share common risk factors, such as dietary habits, lifestyle and socioeconomic conditions .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis found a significant relationship between obesity and dental caries in children from industrialized countries, but the authors concluded that future analyses should focus on common risk factors as confounders in this association [10]. Another recent systematic review and meta-analysis confirmed that, in high-income countries, overweight and obese children had more dental caries when compared to normal-weight children [11]. The authors called for future studies to address confounding factors, including possible common risk factors.…”
Section: Introductionmentioning
confidence: 99%